Strength-Based Approach in Indian Clinical Practice: Reflections from a Five-year Ethnographic Study. Issue 6 (2nd November 2022) - S, Aswini; Deb, A.
ABSTRACT: Background: Research and practice in the area of mental health has been conventionally predominated by the deficit-based approach, which attempts to improve lives by fixing symptoms. However, the growing impact of the positive psychology movement in the last two decades has resulted in incorporation of the strength-based approach into mental health work. Purpose: The objective of this article is to (i) emphasize the efficacy of strength-based approach in the area of mental health (ii) identify shortcomings in the Indian Mental Health System (MHS) (iii) recognize micro-level initiatives in the MHS and (iv) provide recommendations for the future. Method: These objectives are accomplished via reflections obtained from an ethnographic research with participants reporting mental health symptoms. Additionally, opinions gathered from mental health professionals, and government and non-government organizations working in the area were also considered. Results: This work has shed light on the recent micro-level transformations in the system including contextualization of mental illness and treatment, valuing patient's input in the treatment process, and the creation and effective functioning of mental health task-forces. Conclusion: This paper concludes with a four-point recommendation that can help to incorporate the strength-based approach in MHSs for better outcomes.